The role of self-esteem in patients of cosmetologist - Юдін, Михайло Анатолійович (ScienceRise: Medical Science, 2017)
The aim of the work was the revelation of self-esteem in cosmetological patients. Contingent and methods of research. The research was carried out on the base of medical center “CA-Clinic” during 2014 – 2016. The testing included 286 women, who addressed for cosmetological help. Results. The self-attitude of women with low self-esteem, who addressed to the cosmetologist, was disharmonious and was characterized with the high level of self-non-acceptance, lowered self-respect and self-understanding, alienation of subjectively negative features, exaggeration of imperfections, acute self-criticism. In women with high self-esteem the disorder of harmony was manifested by the high level of self-acceptance, exaggeration of positive features and absence of criticism to the negative ones, lowered self-reflection. Conclusions. Cosmetological patients, who have the lowered or high self-esteem form the separate category of clients and need the use of medical-cosmetological arrangements, directed on disharmonic self-attitude